Hanghaus 2 in Ephesos. Die Wohneinheit 7, Textband 1 Baubefund, Ausstattung, Funde - Rathmayr, Elisabeth (Verlag der Österreichischen Akademie der Wissenschaften, 2016)
Contextual analysis of the architecture, the features and the finds of the Imperial Period dwelling WE 7 of Terrace House 2 in Ephesos.